Interactive video analysis to develop learning and assessment of university students' practical and communication skills : final report. - Hands, Beth (Australian Learning and Teaching Council, 2009)
The objective and authentic assessment of practical skills in tertiary settings is a challenge. The project evaluated the usefulness of a video analysis software program as a teaching and/or assessment tool for practical and professional skills in five different undergraduate programs. Barnett's (1989) model of 'reflective thought through action' highlights the importance of reflective observation of an event in order to plan and implement positive behavioural changes. When the practice activities are directly linked with expected skill outcomes then learning is meaningful and reflective practitioners are developed. Further, most Generation Y students better engage in teaching and learning strategies that include recent information and communication technologies. Participants in this project included academics and students from physiotherapy, health and physical education, education, nursing and counselling disciplines. Findings suggested that the video analysis strategy has potential as both a teaching and formative and summative assessment tool and identified solutions to many technical problems that were encountered. Recommendations are included. [Executive summary, ed]